2013
DOI: 10.1186/1475-2875-12-183
|View full text |Cite
|
Sign up to set email alerts
|

Gestational age assessment in malaria pregnancy cohorts: a prospective ultrasound demonstration project in Malawi

Abstract: BackgroundMalaria during pregnancy is associated with an increased risk for low birth weight (<2500 grams). Distinguishing infants that are born premature (< 37 weeks) from those that are growth-restricted (less than the 10th percentile at birth) requires accurate assessment of gestational age. Where ultrasound is accessible, sonographic confirmation of gestational age is more accurate than menstrual dating. The goal was to pilot the feasibility and utility of adding ultrasound to an observational pregnancy ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 38 publications
(42 reference statements)
1
65
0
2
Order By: Relevance
“…Sentinel sites should be equipped with a minimum package of resources to ascertain outcomes accurately, such as PTD. Ultrasound studies to determine EGA would require the ultrasound machine, continuous supplies, and a trained health care worker with months of mentorship [30]. Although gestational age estimation would improve, health care costs in resource-limited settings would rise with unlikely reduction of adverse pregnancy outcomes [31].…”
Section: Discussionmentioning
confidence: 99%
“…Sentinel sites should be equipped with a minimum package of resources to ascertain outcomes accurately, such as PTD. Ultrasound studies to determine EGA would require the ultrasound machine, continuous supplies, and a trained health care worker with months of mentorship [30]. Although gestational age estimation would improve, health care costs in resource-limited settings would rise with unlikely reduction of adverse pregnancy outcomes [31].…”
Section: Discussionmentioning
confidence: 99%
“…Trained health care workers could have an adjunctive role in ultrasound screening for high-risk OB conditions where access to care is limited. There have been several published studies on basic OB ultrasound training courses for health care workers in LMIC 1, 2, 3, 4, 8, 9, 10, 11. Although adequate performance after training is crucial,12, 13 reporting of quality control (QC) activities has been limited.…”
Section: Introductionmentioning
confidence: 99%
“…16,17,31 The original neonatal maturity scores were developed when LMP was the gold standard, and used regression equations or scoring algorithms to predict LMP-based GA. Few studies have validated postnatal clinical assessment compared to early ultrasound GA in LMIC settings. In Malawi, Wylie et al 32 reported that 79% of infants classified as preterm by the Ballard performed by research nurses were full-term according to best obstetric estimate, including ultrasound (ie, 21% PPV). Taylor and colleagues 33 found that the external Ballard performed by midwives correlated poorly with ultrasound GA in the Gambia.…”
Section: Figurementioning
confidence: 99%